2005
DOI: 10.5172/conu.20.1.38
|View full text |Cite
|
Sign up to set email alerts
|

Magnet hospital research pilot project conducted in hospitals in Western Australia

Abstract: The factors causing nurses to leave nursing are well known and published. The main aim of the research pilot project was to explore and describe the reasons that attract nurses to a specific hospital and that motive them to remain working at that hospital. Data were collected through surveys of different categories of nurses working in selected 'Magnet Hospitals' in Perth (Western Australia). Biographical data were analysed through quantitative methods and content analysis was employed to analyze qualitative d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 1 publication
2
5
0
Order By: Relevance
“…homes or elsewhere. Previous studies also showed similar findings that nurses were more satisfied with their jobs when they worked in hospitals that had more highly educated nurses, adequate supportive staffing, and positive practice environments (Clarke & Aiken, 2008;Naude & McCabe, 2005).…”
Section: Discussionmentioning
confidence: 53%
“…homes or elsewhere. Previous studies also showed similar findings that nurses were more satisfied with their jobs when they worked in hospitals that had more highly educated nurses, adequate supportive staffing, and positive practice environments (Clarke & Aiken, 2008;Naude & McCabe, 2005).…”
Section: Discussionmentioning
confidence: 53%
“…The job attributes are based on the literature describing job characteristics associated with nurse retention (Naude and McCabe, 2005;Hayes et al, 2006;Hogan et al, 2007). The attributes and levels are presented in Table 1; the experiment includes 12 attributes, 11 with two levels and one (salary) with four levels.…”
Section: The Choice Experimentsmentioning
confidence: 99%
“…Each job is described in terms of salary and eleven non-salary attributes set at specific levels. The selection of attributes is based on the literature on Magnet Hospitals in the US (Naude and McCabe, 2005;Seago et al, 2001), and reflect characteristics that have been shown to influence the quitting decision and job satisfaction of nurses. We use 4 different levels of salary and 2 different levels of each non-salary attribute as listed in Table 1.…”
Section: Datamentioning
confidence: 99%